Eficiencia agronómica y económica de fertilizantes compuestos en cacao CCN-51 - Marquínez Moncayo, Ángelo Abigail (2021)
This research was carried out in Eloy Alfaro parish, belonging to Chone Canton, its objective was to evaluate the agronomic and economic efficiency of compound fertilizers in CCN-51 cocoa, proving that fertilization is an important aspect, because it increases the yield and the crop profitability. The plant material used in the trial was CCN-51 cocoa, with a density of 2500 plants ha-1, performing a DBCA with 19 treatments and 3 repetitions, that is, 57 experimental units. The computer-statistical tools used were the Infostat and Excel programs where the yields of the different treatments were obtained in graphical form; after this, the agroeconomic evaluation was carried out where the profitability and agronomic efficiency were determined. The results obtained in this research show that the yield of CCN-51 cocoa was not affected by the fertilization dose tested, so the low dose of 444 kg ha-1 is enough to increase productivity, the biological and economic dose more Efficient efficiency was achieved with 444 kg ha-1 of the Ecocacao Plus fertilizer, with a net economic benefit of 5199 USD ha-1, the highest agronomic efficiency of the fertilization depending on the sources was achieved with Yaramilla integrator.